Transparansi Dana Zakat untuk Meningkatkan Kepercayaan Masyarakat terhadap Lembaga Zakat - M. Zidny Nafi' Hasbi (IAIN Syekh Nurjati Cirebon, 2024)
Zakat management institutions need to be evaluated and can provide transparency and accountability of funds to the public. This study aims to determine the pattern of management of zakat funds in zakat management institutions. This study uses a qualitative descriptive method. The study involved the amil zakat institution in the district of sleman, the province of the special region of Yogyakarta. Data were obtained using interviews, observations, and literature studies on research problems. Data analysis used the Miles and Huberman model, namely data reduction, data tabulation, data presentation, and conclusion. The results show that a transparent income and expenditure report will increase the number of funds collected and facilitate the distribution of zakat evenly. In addition, the transparency of zakat funds will increase public trust in zakat institutions. Therefore, this research is expected to provide an overview of zakat institutions to be transparent and accountable for the funds obtained and distributed.